2012
DOI: 10.1111/1742-6723.12007
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating head injury with bilateral eye avulsion due to Himalayan bear bite

Abstract: The Himalayan black bear (Ursus thibetanus or Selenarctos thibetanus), although an omnivore, is more carnivorous than its American counterpart. It is also more aggressive towards humans and is a threatened species because of the deforestation in the Himalayas. Furthermore, poverty, encroachment of the forest, extensive deforestation, lack of education and living near the forest are factors that increase the probability of such animal injuries. We report the case of a 35-year-old woman who suffered a severe pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…5 A case is also reported with penetrating head injury with bilateral eye avulsion. 6 In our study avulsion injury were found to be 8 (16%) and similar study is found where avulsion injury in 18.94% and tissue loss in 9.11% cases.…”
Section: Discussionsupporting
confidence: 84%
“…5 A case is also reported with penetrating head injury with bilateral eye avulsion. 6 In our study avulsion injury were found to be 8 (16%) and similar study is found where avulsion injury in 18.94% and tissue loss in 9.11% cases.…”
Section: Discussionsupporting
confidence: 84%
“… 11 The injury to the eyeballs makes the victim blind to retaliate. 12 The brutal force applied by the bear led to multiple shattering of facial bones involving the maxilla, zygoma, mandible, nasal bones, orbit, frontal, and parietal calvarias along with extensive soft tissue injury. 5 It is common to observe tissue loss to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is the leading cause for eyeball luxation with cases reported in children and adult secondary to surfboard injury, human bite, trauma by blunt or penetrating injury, animal bite, vehicle crush injury and self-enucleation in psychiatric cases (Hindman et al, 2007;Paya et al, 2012, Roka et al, 2012,2013Kosaki et al,2018). The overall visual prognosis is poor in such cases and various methods to salvage the eyeball have been proposed including simple reposition by patient relaxation and fi nger Roka N and Roka Y.B.…”
Section: Discussionmentioning
confidence: 99%